Answers

The Brainliest Answer!
2014-05-01T17:41:56+05:30
X²+px+1)ax³+(0)x²+bx+c                   (ax-ap
               (-)    (-)    (-)
              ax²+apx²+ax
             ----------------------
                    -apx²+(b-a)x+c 
                       (-)         (-)    (-)
                     -apx²-(ap²)x-ap               
                   ---------------------------
                     (b-a+ap²)x+(c-ap)
                    ---------------------------
as it is a factor remainder is zero
so b-a+ap²=0,c-ap=0
p^2= \frac{a-b}{a}=1- \frac{b}{a}
c=ap \\  \frac{c}{a}=p \\ p^2= \frac{c^2}{a^2}= \frac{(a-b)}{a} \\ c^2=a(a-b) \\ c^2-a^2=-ab
                     
2 5 2
2014-05-01T17:43:15+05:30
C²-a²=-ab
is ur answer
1 5 1